Influence of Fixation and Permeabilization on the Mass Density of Single Cells: A Surface Plasmon Resonance Imaging Study - Cheng, Ruoyu; Zhang, Feng; Li, Meng; Wo, Xiang; Su, Yu-Wen; Wang, Wei (Frontiers in Chemistry, 2019)
Fixation and permeabilization of cells and tissues are essential processes in biological techniques like immunofluorescence and immunohistochemistry for cell biology studies. In typical procedures, the biological samples are treated by paraformaldehyde and Triton X-100 to achieve cellular fixation and permeabilization, respectively, prior to the incubation with specific antibodies. While it is well known that the integrity of cell membrane has been broken during these processes, quantitative studies on the loss of cellular mass density and the enhancement of molecular accessibility at single cell level are still rare. In this study, we employed the surface plasmon resonance imaging technique to monitor the mass density change of single cells during sequential fixation and permeabilization processes. We further utilize the osmotic responses of single cells to sugar molecules as an indicator to evaluate the integrity of cell membranes. It was found that, while fixation initially destructed the integrity of cell membranes and increased the permeability of intra- and extra-cellular molecules, it was permeabilization process that substantially induced significant loss in cellular mass density.